A case study on seismic behavior of circular-sectional steel tubular columns filled with concrete of 100% recycled aggregates. (June 2022) - Yang, Yabin; Chen, Gonglian; Wu, Yuxiang; Li, Xingxin; Li, Fenglan; Zhao, Shunbo
Abstract: With the purpose of recycling waste concrete to the maximum extent, the production of new concrete with 100% fine and coarse recycled aggregates (abbreviated as FRAC) is valuable to be developed as a kind of green and economy building material. To utilize the sufficient compressive strength and avoid the shortage of lower tensile strength of the FRAC, using it as the filling concrete in steel tubular columns is a good choice. In this paper, an experimental study was carried out on the seismic performance of ten circular-sectional steel tubular columns by the pseudo-static test. Eight columns were manufactured with different FRAC strength and diameter-to-thickness ratio of steel tube, and two columns were made as reference by filling conventional concrete. The strain of steel tube, load-displacement hysteretic curves and failure patterns of test columns were measured. Results show that the test columns failed at the root with bulge undermining like elephant leg and the yield of steel tube, the FRAC presented a good filling material owing to the combined working with and confinement by the steel tube. Test columns presented good overall seismic performance with a better energy dissipation ability featured by the fully spindle hysteretic curves and the complete enveloping curves. The ductility of FRAC-filled steel tube columns was sufficient at the same level of conventional concrete-filled steel tube column with a ductility index larger than 3.0. Finally, the method for computing the bearing capacity of circular-sectional FRAC-filled steel tubular columns is suggested.